Practical JIRA Administration - Doar, Matthew (O'Reilly, 2011)
If you're familiar with JIRA for issue tracking, bug tracking, and other uses, you know it can sometimes be tricky to set up and manage. In this concise book, software toolsmith Matt Doar clarifies some of the more confusing aspects by answering difficult and frequently asked questions about JIRA administration. Practical JIRA Administration shows you how JIRA is intended to be used, making it an ideal supplement to the extensive documentation already available. The book's chapters are loosely connected, so you can go straight to the information that best serves your needs. Understand the difference between JIRA groups and JIRA project roles Discover what JIRA schemes do, and learn how to maintain them Use a consistent configuration approach to help you use JIRA as a platform Create a workflow from scratch Add, modify, and deactivate users Prepare for a JIRA upgrade, and troubleshoot if necessary Get remote access to JIRA via email, SQL, REST, and other methods.